ANALISIS KINERJA KEUANGAN KOPERASI SIMPAN PINJAM (STUDI KASUS PADA KOPERASI FS UMKM PASAR SUMPIUH) - Resti Marinda Listanti (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This study aims to analyze the finansial performance of the FS UMKM Market Cooperative in Sumpiuh during the 2020-2024 period using key finansial rations, namely liquidity ratios (current ratio and cash ratio), solvency ratios (net worth to debt ratio and total debt to assets ratio), and profitability ratios (return on equity and return on assets). The method used is descriptive quantitative, utilizing secondary data obtained from the cooperative’s financial reports over the past five years. The results show that the current ratio ranged from 100.56% to 108.69%, still below the cooperative’s ideal standard of 125%, indicating an unsafe liquidity condition. The cash ratio averaged 38.19%, which falls into the poor category as it does not fully cover short-term liabilities with available cash. The net worth to debt ratio averaged only 4.81%, far below the healthy standard of 40%, suggesting a high dependency on member loans. The total debt to assets ratio ranged between 92% and 99%, indicating that almost all of the cooperative’s assets are financed by debt. In terms of profitability, the average ROE was 7.60% and ROA was 4.64%, both still below ideal standards, showing that the cooperative's ability to generate profits from its equity and assets remains suboptimal.